Answer:
Step-by-step explanation:
We have two points (0,6) and (1,11) and to find the exponential function that passes through that points we have to substitute them in the equation [tex]f(x)=b.a^{x}[/tex].
First we are going to replace the point (0,6) in the equation, where x=0 and y=6.
Remember: [tex]a^{0}=1[/tex]
We got the value of b and it's 6. The equation now is:
Finally we have to replace the point (1,11),
Remember: [tex]a^{1}=a[/tex]
Isolating the variable a:
We have then, a=1.83 and b=6. Replacing a and b in [tex]f(x)=b.a^{x}[/tex]
We obtain: